2018
DOI: 10.1007/s12028-018-0651-4
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Vascular Changes During Acute Intracranial Pressure Drop

Abstract: Objective: This study applied a new external ventricular catheter, which allows intracranial pressure (ICP) monitoring and cerebral spinal fluid (CSF) drainage simultaneously, to study cerebral vascular responses during acute CSF drainage.Methods: Six patients with 34 external ventricular drain (EVD) opening sessions were retrospectively analyzed. A published algorithm was used to extract morphological features of ICP recordings, and a template-matching algorithm was applied to calculate the likelihood of cere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 60 publications
(82 reference statements)
0
8
0
Order By: Relevance
“…1992; Liu et al . 2019). The role of ICP in mediating sympathetic discharge is supported in subarachnoid haemorrhage patients with early brain injury leading to increases in ICP, and deceased CBF (Zhang et al .…”
Section: Sympathetic and Parasympathetic Control Of Cerebral Blood Flowmentioning
confidence: 99%
“…1992; Liu et al . 2019). The role of ICP in mediating sympathetic discharge is supported in subarachnoid haemorrhage patients with early brain injury leading to increases in ICP, and deceased CBF (Zhang et al .…”
Section: Sympathetic and Parasympathetic Control Of Cerebral Blood Flowmentioning
confidence: 99%
“…Using MOCAIP technology, Asgari et al found reliable changes in ICP MOCAIP morphology in response to CO 2 inhalation, and with the morphologic template matching method were able to develop a standardized metric for assessment of VCI and VDI 11 16. These indices have been validated across several different patient cohorts and have shed insights into autoregulation and dynamic cerebral vascular changes which occur after cerebrospinal fluid drainage 11 13. Our study is the first to employ a similar template matching method for assessment of cerebral blood vessel dilation and constriction in response to EVT in patients with aneurysmal SAH and vasospasm.…”
Section: Discussionmentioning
confidence: 66%
“…In this study, we applied a validated algorithm, morphological clustering and analysis of ICP (MOCAIP) algorithm, to extract the morphological features of an ICP pulse, including pulse amplitude, time intervals among subpeaks (P1, P2, P3), curvature, slope, and decay time constants (shown in online supplementary doc 1). 10 12 13 16 17 In general, consecutive raw ICP pulses are segmented and then clustered into distinct groups based on their morphological distance; by doing this, the noise and artifacts can be excluded; then the largest cluster is identified and the averaged pulse of this largest cluster calculated and termed the dominant ICP pulse 18. A reference library of validated ICP pulses is used to recognize legitimate dominant pulses,12 and then the MOCAIP algorithm is used to perform a comprehensive search for all landmark points on an ICP pulse and use them as candidates for designating the three subpeaks.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations